Non-adiabatic effects in F + CHD3 reactive scattering - Palma, Juliana Isabel (2017)
The effect of non-adiabatic transitions on the F(2P) + CHD3(ν1) → DF + CHD2 and F(2P) + CHD3(ν1) → HF + CD3 reactions is investigated. The dynamics of the nuclei was simulated using trajectory surface hopping and a vibronically and spin-orbit coupled diabatic potential energy matrix. To facilitate the calculations, the fewest switching algorithm of Tully was adapted to the use of a complex diabatic potential energy matrix. For reactions of CHD3 with ground state fluorine atoms, F(2P3/2), the ratio between the previously computed adiabatic cross sections and the non-adiabatic ones was found to range from 1.4 to 2.1. The actual ratio depends on the translational energy and the initial vibrational state of CHD3. The total reactivity of CHD3(ν1 = 1) was found to be always larger than that of CHD3(ν1=0) mainly because of the increase in the cross sections for the HF + CD3 channel. Thus, the inclusion of non-adiabatic transitions in the theoretical treatment cannot resolve the existing disagreement between theory and experiment. Cross sections for the reaction of CHD3 with spin-orbit excited fluorine atoms, F(2P1/2), were found to be significantly smaller than the ones for reaction with F(2P3/2).